Dynamics of magnetic system formed by two semi-skyrmions in circular nano-pillars with a perpendicular anisotropy. (26th January 2023) - Zhang, Wenbo; Hou, Zhiwei; Zhang, Hong; Luo, Yanwei
Abstract: Magnetic skyrmion has the advantages of stable topology and small volume. Many researchers choose different materials or build double free layers for using skyrmions in spin torque nano-oscillators capable of producing GHz frequencies. In this paper, the dynamics of the two semi-skyrmions in a circular nano-pillar with perpendicular magnetic anisotropy free layer and a spin polarizer are studied using micromagnetic simulation. The oscillation frequency of two semi-skyrmions is more than two times higher that of the single semi-skyrmion. In addition, we also explore the influences of different parameters (current density, damping coefficient, anisotropy constant, and temperature) on the motion of two semi-skyrmions. The results show that damping coefficient and exchange interaction constant have the most pronounced influence on the oscillation frequency of the system.